High-resolution climate of the past ∼7300 years of coastal northernmost California: Results from diatoms, silicoflagellates, and pollen. (10th March 2018) - Barron, John A.; Bukry, David; Heusser, Linda E.; Addison, Jason A.; Alexander, Clark R.
Abstract: Piston core TN062-O550, collected about 33 km offshore of Eureka, California, contains a high-resolution record of the climate and oceanography of coastal northernmost California during the past ∼7.34 kyr. Chronology established by nine AMS ages on a combination of planktic foraminifers, bivalve shell fragments, and wood yields a mean sedimentation rate of 103 cm kyr −1 . Marine proxies (diatoms and silicoflagellates) and pollen transported by the nearby Eel River reveal a stepwise development of both modern offshore surface water oceanography and coastal arboreal ecosystems. Beginning at ∼5.4 cal ka the relative abundance of coastal redwood pollen, a proxy for coastal fog, displays a two fold increase suggesting enhanced coastal upwelling. A decline in the relative contribution of subtropical diatoms at ∼5.0 cal ka implies cooling of sea surface temperatures (SSTs). At ∼3.6 cal ka an increase in the relative abundance of alder and oak at the expense of coastal redwood likely signals intensified riverine transport of pollen from inland environments. Cooler offshore SSTs and increased precipitation characterize the interval between ∼3.6 and 2.8 cal ka. A rapid, stepwise change in coastal climatology and oceanography occurs between ∼2.8 and 2.6 cal ka that suggests an enhanced expression of modern Pacific Decadal Oscillation-like (PDO) cycles. A three-fold increase in the relative abundance of the subtropical diatom Fragilariopsis doliolus at 2.8 cal ka appears to mark an abrupt warming of winter SSTs. Soon afterwards at 2.6 cal ka, a two fold increase in the relative abundance of coastal redwood pollen is suggestive of an abrupt intensification of spring upwelling. After ∼2.8 cal ka a sequence of cool-warm, PDO-like cycles occurs wherein cool cycles are characterized by relative abundance increases in coastal redwood pollen and decreased contributions of subtropical diatoms, whereas opposite proxy trends distinguish warm cycles. Graphical abstract: